Effects of ambient temperature on physical and physiological demands and player`s judgment ability assessed by a football-specific fatigue-inducing protocols - Pompeo, A.; Cirillo, E.; Costa, J.; Vilaça-Alves, J.; Williams, A. M.; Ramirez-Campillo, R.; Neves, J. A.; Casanova, F. (Journal of Human Sport & Exercise, 2023)
We systematically reviewed the effect of ambient temperature on football players` performance during a football-specific fatigue protocol. Data sources: Cochrane Library, PubMed, Scopus, SPORTDiscus, Web of Science. Eligibility criteria followed the P.I.C.O.S. approach: (i) Healthy football players regardless of sex, age, or competitive level; (ii) football-specific fatigue-inducing protocol followed by assessment of anticipatory judgments, under controlled temperature conditions; (iii) Comparison groups using a different temperature during the foot-ball-specific fatigue-inducing protocols; (iv) Outcomes included measures of anticipation, and/or physical or physiological tests; (v) No limitations regarding study design, if (ii) and (iii) were present. The searches resulted in 1,289 titles. However, none of the articles met the P.I.C.O.S. adopted, resulting in a total of zero eligible articles for the systematic review. Therefore, from a critical review of the existing literature, it must be concluded that evidence bases of sufficient scientific quality for the understanding the effect of temperature on physical and physiological demands and anticipatory judgments of football players is simply lacking. This should strongly motivate the scientific community to engage in research on the topic, to test if theoretical assumptions are accurate.